A quasi-experimental synthetic control evaluation of a place-based police-directed patrol intervention on violent crime - Rydberg, Jason (Journal of experimental criminology, 2018)
This research evaluates the impact of an implementation of a place-based police-directed patrol intervention—originally based on the Data Driven Approaches to Crime and Traffic Safety (DDACTS) model—on violent crime in Flint, Michigan, USA.